Analysis of property investment in Singapore - Chen, Yizhe (Nanyang Technological University, 2024)
The property market in Singapore has a long history since the mid of 1800s after the British built a port here and slowly Singapore becomes a transport and trading hub in Southeast Asia. After Singapore became independent, government had invested heavily on the infrastructure in order to attract more talents and investors come to Singapore.This report will introduce the background, introduction, different policies and analysis on the private properties for both locals and foreigners. The objective is to help the investors to understand better for the pros and cons for the properties investment in Singapore.